Blog content management in shaping pro recreational attitudes - Stepaniuk, Krzysztof (Journal of Business Economics and Management, 2017)
The main aim of this article was to research the impact of the content of recreational blogs on the change of attitude and behaviours of their recipients, as well as creating the basis to manage the content of blogs directed to achieve particular results. The study was conducted with the use of quantitative and qualitative content analysis. The contents of 691 comments left by 4 main types of commentators were analysed. The evaluation of individual entries was performed using the assumptions of the modified AIDA model of consumer behaviour. The possibility of a positive causal link between the presented content and the appearance of the signs of its impact on the behaviour of individuals tracking the posts has been proven to a minor extent only. Merely 0.5% of commentators and individuals were not engaged in running declared changing their way of life to a pro recreational and sports-related one. Conducting analyses directly on the large, narrative story-telling content with the use of a consumer behaviour model is a novelty of this paper and rarely appears in the scientific literature. The theoretical significance of the work is connected with the development of the theory of marketing management in the context of social networks content management.